OPTIMASI PENGGUNAAN TEKNOLOGI ALAT MESIN DALAM MENDUKUNG PRODUKTIFITAS PETANI DI KECAMATAN GALUR - Santosa, Agus Djoko (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
The optimation of mechanism technology for land cultivation on Galur District in Kulon Progo Yogyakarta to be implementation becaused the decreased of the man la-bour for land preparation. The needs of the land preparation must be continued with me-chanism technology. The Needs of mechanization technology be calculate with linier pro-gramming. The Goal of the calculate are Rotary must be increased 4 units, and without moald board plow, Financial analysis to feasibility of the needs of the mechanism, and the decision of the chose implement for land preparation with Promethee method. And the goals of the research are mechanism technology sustainable on Galur District are needs for much farmer